Comprehensive comparisons between frequency‐domain analysis and time‐domain analysis for LLC resonant converter. Issue 9 (4th May 2020) - Wei, Yuqi; Luo, Quanming; Mantooth, Alan
Abstract : LLC resonant converter has been widely used in many applications due to its characteristics of high efficiency and high frequency characteristics. Analysis method plays great role in converter design and operation performance. For LLC resonant converter, the most frequently used analysis methods are frequency‐domain analysis (FDA) and time‐domain analysis (TDA). FDA assumes that only fundamental harmonics can deliver energy in the system, while TDA is obtained by solving circuit state equations. In this study, comprehensive and complete comparisons between FDA and TDA in terms of analysis methodology, parameter design, analysis accuracy, conduction loss, other power losses, and system efficiency are implemented. The analysis and comparison results show that under the same system specifications, by adopting TDA, a larger magnetising inductance value can be used when compared with FDA, which will reduce the resonant tank circulating current and increase the system efficiency. The comprehensive analysis can provide guidance for engineers when analysing and designing LLC resonant converter. Finally, a 200 W experimental prototype was built and tested to verify the theoretical analysis.